How Select Strength and Power Measures Relate to FCS Football On-Field Performance - Seth Long; Nanette V. Lopez; Jay T. Sutliffe; Dierdra Bycura; Jessica R. Szczepanski; Scott N. Drum (Journal of Functional Morphology and Kinesiology, 2025)
Objective: Understanding unique ways that strength and power contribute to on-field performance in collegiate-based American football might aid coaches in recruiting and determining starters. Using retrospective analysis of existing data, including starting status (STR) and number of defensive tackles or contributing plays (CP), we sought a viable strategy to observe on-field play. Our purpose was to determine what role baseline and in-season strength, and power metrics contributed to on-field football performance (e.g., using STR and CP) from one Football Championship Subdivision (FCS) university. We hypothesized greater pre-season (baseline) and in-season (repeated variables) strength and power outcomes would lead to an increased number of STR among players (n = 53) as well as CP among defensive players (n = 30). Method: Power, determined through countermovement jump (CMJ) was observed weekly using a VALD Performance force deck (i.e., jump height) over a 9-week, in-season period (excluding weeks 6 and 8, a bye week, and erroneous data, respectively). Baseline measures of strength and power were also collected at the beginning of the season for each player using four specific measurements, namely the following: (a) peak vertical jump; (b) pull-ups to failure; (c) a one rep max for bench press; (d) power clean. Pearson’s correlation was used to correlate baseline measures and weekly power, along with baseline measures and the total number of STR and CP each week. Additionally, linear regressions were used to examine the effects of baseline measures (vertical jump, bench press) on STR and CP. Results: Moderate correlations (r > 0.5) were observed between baseline variables and weekly CMJ measures. Baseline measures of power clean were correlated with CP only in week 4. All other analyses were not significant. Conclusions: Since our on-field performance variables were not significant, future research should focus on more potent variables, as reported in the literature, such as football IQ, initial recruiting status, and psychological resilience, in addition to accounting for strength and power metrics.